The Overview of Eating Patterns and Dental Caries Status of The Community of Pendul, Argorejo, Bantul Yogyakarta - Sri Utami; Retnaningtyas Pinastika; Novitasari Ratna Astuti; Arya Adiningrat (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2023)
The primary caries etiology factors are hosts (teeth), agents (microorganisms), substrates, and time. Individual characteristics can be influenced by caries' risk factors, such as age, education level, economic status, and diet. The high frequency of food and snack consumption, especially cariogenic food, is riskier of being caries affected. This study aims to describe the eating pattern and dental caries status of the Pendul community in 2018. This research is a descriptive observational study with a cross-sectional approach. It was held from December 2018 to January 2019 in the Pendul district of Bantul. The subject of this research was selected using the accidental sampling method with 138 respondents. The research instrument employed the Food Frequency Questionnaire and DMFT index. The result showed that the higher the consumption of cariogenic foods is, the higher the caries index will be. The highest frequency of cariogenic foods consumption was snacks, with a mean DMFT index of 8,02. The highest frequency of cariogenic beverage consumption was sugar tea, with a mean DMFT index of each respondent was 8 teeth. The highest frequency of cariogenic consumption per week lay in snacks and packaged tea.  Apart from the four etiological factors, such as agent, host, substrate, and time, caries can also be caused by other determinant factors such as gender, age, education level, and socioeconomic status.